Perkin-Elmer fluorescence spectrophotometer in use at Arthur D. Little company - Perkin-Elmer Corporation (1970)
General view of two unidentified chemists discussing the spectrum of a compound analyzed using a Perkin-Elmer fluorescence spectrophotometer in the laboratory of the Biomolecular Sciences Section of the Arthur D. Little Company. Per notations accompanying the photograph, the analysis is used to determine therapeutic indexes of anti-cancer drugs as part of a research program conducted on behalf of the National Cancer Institute.
Keywords: Women in science; Perkin-Elmer Corporation; Scientific apparatus and instruments; Corporations; Women chemists; Arthur D. Little, Inc.; Drugs; Drugs--Research; Cancer--Research; Fluorescence spectroscopy; Laboratories; Chemists